The Influence of Breakfast Quality on Blood Sugar Levels of Clients with DM Type 2 - Irine Christiany; Kiaonarni Ongko Waloya; Adin Mu’afiro (Health Notions, 2017)
Breakfast quality is an overview of diet and food composition which client with DM Type2 aims to find the right type, amount, and schedule as the principles of diet for DM to keep the blood sugar levels stable. The research method was cross sectional study. The population was all patients in Geriatric Unit of Gundih Public Health Center in Surabaya who already diagnosed with DM Type2, taken randomly (simple random sampling). Dependent variable was blood sugar levels of client with DM Type2. Independent variable was the quality of breakfast. The research instrument was a questionnaire and a food recall 1 x 24 hours. Data analysis was using logistic regression test. The results of the analysis of data showed that the blood sugar levels of the clients with DM Type 2 was influenced by the amount and schedule of breakfast. Keywords: Breakfast quality, Type, Amount, Schedule, Blood sugar levels, DM Type 2